Acute oral toxicity study of novel polyherbal formulations by using wistar rats and Swiss albino mice as per OECD 425 TG - Ramkishan Jatoth; S.P Dhanabal; V. Senthil; T. Ganesh; Jubie Selvaraj; P.S. Venkatesan (Phytomedicine Plus)
Background: Hydaljss08 is a new semisolid fermented hydroalcoholic polyherbal formulation containing crude drug substances. Immunoboost Tab is a novel polyherbal dosage form that is incorporated isolated, and fractionated phytochemical substances. Acute oral toxicity is a primary safety profile of the novel polyherbal formulations. As a part of our study, we estimated acute toxicity safety profile of novel dosage forms by a Swiss albino mice and Wistar rats. Aim: According to the OECD 425 test guideline., the study aims to estimate acute toxicity tests of the “Hydaljss08, and Immunoboost Tab” dosage forms in rats and mice to assess the safety profile. Mice and rats are normally used in safety studies because of their susceptibility to toxic challenges, tumor induction, and carcinogenicity. Material and Methods: 1 % CMC, Hydaljss08, Immunoboost-Tab polyherbal formulations, female rats, and albino mice. Animals were divided into the control groups, and treated groups with test dosage forms. At the end of the study, animals were euthanized by using the CO2 asphyxiation technique and subjected to gross pathological examinations. Results: According to the assessment of the experimental data, the single-dose acute toxicity study of Hydaljss08 and Immunoboost-Tab formulations in mice and rats was fine. No signs of toxicity were observed in the animals treated at (2000 mg/kg.b. wt, Po), and revealed dullness, causing lethargy, and piloerections, which only persisted on the 1st day. At the end of the study, mild congestion in the liver, and lungs was observed in animals, treated with “Hydaljss08 formulation” compared to the vehicle control groups. Conclusions: The estimated LD50 of Hydaljss08, and Immunoboost-Tab polyherbal formulations in rats and mice by oral route was found >2000 mg/kg, b.wt.